Penerapan Metode Diskusi Daring pada Masa Pandemic COVID-19 untuk Meningkatkan Kemampuan Komunikasi Mahasiswa Calon Guru - Hikmawati Hikmawati; Naswan Suharsono; Wayan Mudana (Indonesian Publication Center, 2020)
Limited trial research has been conducted on the application of online discussion methods during the COVID-19 pandemic to improve the communication skills of prospective teacher students. The subjects of this study were 58 prospective teacher students who attended the Study and Learning lectures in the 2020/2021 Academic Year at the Physics Education Study Program, Mataram University. Online discussion topics include learning theories, namely the theory of learning behavior, cognitive, constructivist, humanistic, cybernetics, revolution-socio-cultural, and multiple intelligences. The instrument used in this study was a student teacher communication skill assessment sheet. The communication skills assessed consist of 3 indicators, namely the ability to answer questions, the ability to communicate ideas with symbols or tables, and the ability to work together in groups. Assessment of student teacher communication skills is obtained through observations in Lecture activities of Study and Learning as much as 14 meetings. The assessment score for each indicator of communication skills uses a scale of 4. The average value of the ability to answer questions is 3.10 (good criteria), the ability to communicate ideas with symbols or tables is 3.00 (good criteria), and the ability to work together in groups is equal to 3.18 (good criteria). Thus, the application of the online discussion method during the COVID-19 pandemic can improve the communication skills of prospective teacher students with the highest indicator, namely the ability to work in groups.